THE IMPORTANCE OF THERMAL INSULATION MATERIALS IN BUILDINGS - U.Q.Toshmatov; X.T.Jamoliddinova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The role of thermal insulation materials in buildings cannot be overstated, as they significantly contribute to energy efficiency, occupant comfort, and environmental sustainability. This article aims to highlight the importance of thermal insulation materials in buildings by discussing their impact on reducing heat transfer, minimizing energy consumption, and improving indoor climate control.